2015
DOI: 10.1111/zoj.12275
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy reveals six new species related to the Mediterranean corn stalk borerSesamia nonagrioides(Lefèbvre) (Lepidoptera, Noctuidae, Sesamiina)

Abstract: 244Species in the stem borer noctuid subtribe Sesamiina are notoriously difficult to distinguish because most related species have homogeneous wing patterns and almost indistinguishable genitalia. The latter is potentially problematic because this group includes several important pest species that are usually baregly distinguishable from non-pest species. In this study we focus on the Mediterranean corn stalk borer Sesamia nonagrioides (Lefèbvre), an important pest of maize with a wide area of distribution tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 84 publications
0
80
0
Order By: Relevance
“…In phytophagous insects, host plant, habitat fragmentation, reproductive system, dispersal capacity and geographical or reproductive barrier are reported as the main drivers of genetic structure [16, 17, 69]. In this study, no conclusion can be drawn regarding host plant as only two genera ( i .…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In phytophagous insects, host plant, habitat fragmentation, reproductive system, dispersal capacity and geographical or reproductive barrier are reported as the main drivers of genetic structure [16, 17, 69]. In this study, no conclusion can be drawn regarding host plant as only two genera ( i .…”
Section: Discussionmentioning
confidence: 86%
“…This was further confirmed by the analysis of 16S sequences [53] and the PTP analysis. Although the PTP procedure is not error-free and the resulting species delimitation is putative [29], this method has been implemented in several recent studies [17, 5457] and the procedure appears to be quite robust to different phylogenetic methods [58]. Furthermore, the high genetic diversity observed across North America both on mtDNA and microsatellite markers is also compatible with the idea of a native area on this continent [59, 60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the European population may have originated either from such pioneer populations expanding to the northern Mediterranean from East Africa (Arabian Peninsula) or from West Africa following a forceps-like colonisation. However, this scenario of unique colonization of the Palaearctic region from East Africa as suggested recently by Kergoat et al (2015) requires more studies to be confirmed.…”
Section: Discussionmentioning
confidence: 91%